INVESTIGATING THE EFFECT OF FLASHCARD ON GRADE SEVEN STUDENTS’ VOCABULARY ACQUISITION - Hanafi Wibowo; Siti Yuniarti (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2017)
This research principally aims to find out whether or not there is significance effect of using flashcard on students’ vocabulary acquisition. the research was conducted from 3th to 29th November 2016 at SMPN 45 Bekasi, in the Academic Year of 2016/2017.The research methodology adopted was quasi experimental method, with the research design being randomized post test only control group design. The statistic method used to analyze the data was ANOVA using SPSS through the testing of Null Hypothesis, which was preceded by the normality and homogeneity test as the pre-requisite to the data analysis. The result of ANOVA showed significance value was 0,000, which was lower than 0,05, and that Fobserved ( 35,926 ), which was higher than the critical value of Ftable (at the significance level of 0.05 and df = 1/58, namely 3.982. Accordingly, the Null Hypothesis (Ho), stating that there is no effect using flashcards on students’ vocabulary acquisition at SMPN 45 Bekasi, was rejected and the Alternative Hypothesis (Ha), stating that there is significance effect using flashcards on students’ vocabulary acquisition at SMPN 45 Bekasi was accepted.On the basis of the rejection of Ho and acceptance of HA, it can be concluded that flashcards has significance effect on students’ vocabulary acquisition at SMPN 45 Bekasi. In other words, the research has empirically proved that there is significance effect of using flashcard on students’ vocabulary acquisition at SMPN 45 Bekasi.